Association between smoking and health outcomes in an economically deprived population: the Liverpool Lung Project. Issue 8 (17th April 2017) - Sherratt, F C; Field, J K; Marcus, M W
Abstract : Background: The association between smoking and several health outcomes among those from the most deprived communities in the UK has not previously been detailed. The aim of this study is to examine the impact of smoking on health outcomes specifically among a particularly deprived population in a developed country (Liverpool; one of the most deprived local authorities in England). Methods: The Liverpool Lung Project recruited a prospective cohort of 8753 participants from across Liverpool, aged 45–79 years between 1998 and 2008. Participants were followed annually through the Hospital Episode Statistics until 31 January 2013. Logistic regression models were used to identify health outcomes of smoking. Results: From our study population, 5195 were smokers and 3558 were non-smokers. Smoking was associated with male gender (OR 1.62, 95% CI 1.48 to 1.77), pneumonia (1.28, 95% CI 1.10 to 1.49), chronic obstructive pulmonary disease (1.30, 95% CI 1.14 to 1.48), emphysema (5.46, 95% CI 3.48 to 8.55), bronchitis (1.85, 95% CI 1.65 to 2.07), other cancers (1.69, 95% CI 1.44 to 1.99), lung cancer (6.0, 95% CI 3.72 to 9.69), diabetes (1.21, 95% CI 1.02 to 1.43) and cardiovascular disease (1.45, 95% CI 1.25 to 1.67). Conclusions: Smokers from deprived backgrounds in Liverpool showed increased risk of developing pneumonia, emphysema, chronic obstructive pulmonary disease, bronchitis, lung cancer, other types of cancer, cardiovascular disease and diabetes. These findings are in line with the literature and may help to inform public health policies and ultimately work towards addressing smoking-related health inequalities.